UNDERSTANDING AND EVALUATING PERSONAL LETTER WRITING: A SYSTEMIC FUNCTIONAL LINGUISTICS ANALYSIS OF STUDENT TEXTS IN ONE OF SENIOR HIGH SCHOOL IN INDONESIA - Alfira Veronica Mangana; Eri Kurniawan (University of Kuningan, 2020)
Based on 2013 Curriculum, Personal Letter can be considered as one of the challenging text types that should be mastered by the students. This might be the reason why the text is taught in Senior High School Level. Therefore, it is crucial for the teachers to expand their knowledge regarding this type of genre to overcome students’ problems faced during writing personal letter. This study is aimed to analyse student’s Personal Letter text based on three metafunctions in SFL perspective. It is expected that by identifying students’ problems, teachers can decide and design appropriate pedagogical plan. The data of this descriptive qualitative study were analysed by using three metafunctions in Systemic Functional Linguistics (SFL). The result of the study reveals that the student’s major problems in producing Personal Letter text are the use of subject and verb tense (interpersonal metafunctions), the generic structure of the text, the use of conjunctions, the grammatical errors, and L1 interference.Keywords: personal letter; systemic functional linguistics; metafunction; discovery learning strategy.